NEPHROLYSIS PATHOPHYSIOLOGY: MECHANISMS AND CLINICAL IMPLICATIONS - SHODIEV ULMAS MUSTAFOEVICH (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Nephrolysis  is  a  surgical  procedure  involving  the  dissection  of  perinephric adhesions surrounding the kidney, often performed to treat obstructive uropathy or chronic flank pain caused by fibrosis. Although frequently successful, the underlying pathophysiological mechanisms leading to the need for nephrolysis—such as chronic inflammation, retroperitoneal fibrosis, and ischemia—are complex and multifactorial. This  article  explores  the  biological  and  molecular  pathways  that  contribute  to perinephric adhesion formation and reviews the clinical consequences and outcomes of nephrolysis.